Preaching: An initial theoretical exploration - Pieterse, Hennie; Wepener, Cas (Hervormde teologiese studies, 2021)
In this article, the event of preaching was explored by making use of both older and newer sources. Whilst taking cognisance of continuous contextual changes and developments within the discipline of homiletics, core hermeneutical, theological and homiletical aspects of preaching are revisited. The aim of this exploration was to formulate a preliminary theory of preaching that can be revisited and revised as part of a larger empirical homiletical investigation, which makes use of Grounded Theory. Contribution This article adhered to the journal's scope and vision by its focus on a theoretical reflection on the practice of preaching at the intersection of theology, hermeneutics and homiletics.